The Effect of Ketamine-Zolazepam-Tiletamine and Ketamine-Diazepam Anesthesia Combination on Physiological Features of Dog Castration (Canis Familiaris) - Darang, Calvin Lummu; Utami, Tri; Tophianong, Tarsisius Considus (Jurnal Veteriner Nusantara, 2025)
Castration in male dogs is a medical procedure aimed at reducing the population of male dogs. The purpose of this study was to determine the physiological profile of administering a combination of ketamine-zolazepam-tiletamine and ketamine-diazepam during castration. Six domestic male dogs weighing 8-15 kg and aged 6 months to 1 year were used in this study. Physiological observations of heart rate, respiratory rate, body temperature, digit reflex, and pupil reflex were statistically analyzed using an independent t-test. The oral mucosa was observed descriptively. Statistical analysis results showed that heart rate in group K1 with ketamine administration (10 mg/kg bw, iv) – zolazepam-tiletamine (5 mg/kg bw, iv) and K2 with ketamine (10 mg/kg bw, iv) and diazepam (0.2 mg/kg bw, iv) from T0 to T60 showed significant differences (P<0.05). Respiratory rates in groups K1 and K2 at T0, T10, T40, T50, and T60 showed significant differences. Body temperature and pupillary reflexes in groups K1 and K2 showed no significant differences. Dog digit reflexes in groups K1 and K2 showed significant differences. The combination of ketamine-zolazepam-tiletamine (KZT) and ketamine-diazepam (KD) caused an increase in heart rate and respiratory rate from normal values, but the increase in KD was closer to normal limits. Body temperature was within normal limits when KZT and KD combinations were administered. The loss of digit reflex and pupil reflex responses with the KZT combination lasted longer than with KD, indicating that the analgesia and sedation quality of KZT was deeper than that of KD. The oral mucosa in the KZT and KD combinations was pink, and the Capillary Refill Time (CRT) was < 2 seconds from T0 to T60.